One-pot three-component synthesis and photophysical properties of highly fluorescent novel 4-alkyl-3-aryl-2,6-dicyanoanilines by using tris(hydroxymethyl)aminomethane as a catalyst - Kudale, A. S.; Kamble, S. B.; Gore, A. H.; Pisal, M. M.; Salokhe, A. T.; Kolekar, G. B.; Helavi, V. B. (Chemical Data Collections, 2019)
Novel 4-alkyl-3-aryl-2,6-dicyanoanilines were synthesized by a multi-component one-step reaction of aromatic aldehyde, malononitrile and aliphatic aldehyde using tris(hydroxymethyl)aminomethane (THAM) as a catalyst under microwave (MW) irradiation or conventional heating. The optimized reaction condition involved use of 2.5 equivalents of THAM under MW irradiation at 140 W using 20% MW power for 5 min or conventional heating at 80 °C for 8 h in dimethylformamide. The photophysical properties including λmax, quantum yield and Stokes’ shifts of newly synthesized molecules were studied. All compounds exhibited quantum yield in the range of 0.04–0.52 with respect to standard quinine sulphate having quantum yield 0.54. The Stokes’ shifts of all compounds were found in the range of 41–105 nm. The current strategy provides operationally simple protocol using THAM as a catalyst to synthesize 4-alkyl-3-aryl-2,6-dicyanoanilines with diverse structural features to make them available for exploration of their photophysical as well as biological applications.